Penerapan Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah (SAK EMKM) dalam Penyusunan Laporan Keuangan pada Toko Dzawata Trophy Pekanbaru, Riau: Perspektif Akuntansi Syariah - Atika Sukma; Rahmi Isriani (Lembaga Yasin AlSys, 2026)
The application of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in preparing MSME financial statements has received attention in various previous studies. However, studies that specifically discuss the implementation of SAK EMKM in micro-enterprises from the perspective of Islamic accounting remain limited. This study aims to analyze the application of SAK EMKM in preparing financial statements at Toko Dzawata Trophy Pekanbaru, Riau, viewed from the perspective of Islamic accounting. This study used a qualitative approach with a case study design, involving one key informant, namely the owner of Toko Dzawata Trophy, who was selected using purposive sampling. Data were collected through observation, in-depth interviews, documentation, and literature review, and were then analyzed using the interactive analysis model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results show that the preparation of financial statements at Toko Dzawata Trophy is not yet fully in accordance with SAK EMKM because recordkeeping is still limited to cash receipts and disbursements, has not yet included a statement of financial position, income statement, and notes to the financial statements, and there is still a mixing of personal and business finances. These findings contribute to the development of studies on the implementation of SAK EMKM through the integration of Entity Theory and the Islamic accounting perspective in MSME financial management. The conclusion of this study emphasizes the importance of applying SAK EMKM and Islamic accounting principles in improving the quality of financial reporting, transparency, and accountability of MSMEs. The implications of this study include theoretical contributions to the development of Islamic accounting literature as well as practical implications for MSME actors and mentoring institutions in improving competence in preparing financial statements in accordance with standards. Future research is recommended to expand the research object and examine the factors that influence the implementation of SAK EMKM in various MSME sectors.